CLAIM, DATA AND WARRANT USED IN JUSTIN TRUDEAU’S SPEECHES - Nurfia Maliza; Tria Novita Br Karo Sekali; Dharmadiah Dharmadiah; Rifky Sultan Nico; Diana Sopha (PHILOLOGY Journal of English Language and Literature, 2023)
This study aims to determine the elements of argumentative writing in the form of claims, data and warrants in 5 speeches by Canadian President Justin Trudeau entitled "Prime Minister's Remarks in Tribute to the Honorable Jim Carr, Prime Minister's remarks at the B20 Summit in Bali Indonesia, Speaking notes for the National Statement of Canada at the Summit of the Americas, The Prime Minister and federal ministers announce gun control measures and Prime Minister's remarks introducing President Zelensky in the House of Commons.” The method used in this research is a qualitative method with a descriptive type. The results of this study indicate that there are 84 elements of argumentative writing consisting of 28 claims, 28 data, and 28 warrants.